Smart grid system / Abdul Rahman Musrael - Musrael, Abdul Rahman (2024)
The power grid system, an essential network for delivering electricity from power plants to consumers, comprises generation, transmission, and distribution components. Power plants produce electricity, transmitted via high-voltage lines to substations near populated areas, where voltage is reduced for distribution to homes, businesses, and industries. Balancing supply and demand in real-time and maintaining stability in frequency and voltage levels. The objective of this final year project is to modernize the existing grid system by implementing a smart grid that utilizes microcontrollers for efficient energy management and continuous monitoring. Recognizing the growing demand for sustainable energy solutions, the project aims to offer a cost-effective alternative by harnessing Internet Of Things (IoT) technologies. To gather and analyse data effectively, the system integrates sensors like volage sensor and current sensor with communication modules. The key component of the system is the microcontroller, equipped with sophisticated algorithms for data collection. Users are empowered with the ability to monitor energy trends, assess power utilization, and customize settings through an intuitive interface that provides real-time data access and system administration. Through the integration of IoT and ESP32 technology, the proposed smart grid system presents a smart and environmentally friendly energy management framework. By leveraging these advancements, the project endeavours to not only enhance the efficiency and reliability of the power grid but also contribute to the broader goal of sustainability in energy consumption and management.